Standard Breton, Traditional Dialects, and How They Differ Syntactically. (1st January 2020) - Jouitteau, Mélanie
This article provides a first attempt of a syntactic characterization of the different Breton varieties spoken in the twenty-first century. Standard Breton is addressed as one of the modern dialects spoken in Brittany, and its syntax is compared with that of traditional varieties. I first establish a baseline and inventory the syntactic parameters that differentiate the traditional dialects from each other: Kerne, Leon, Goelo, Treger (KLT in the West) and Gwenedeg (South East). I show that a robust body of syntactic variation characterizes traditional dialects. I next compare these with the Standard variety that emerged during the twentieth century, and show that if Standard Breton has original features of its own, it varies less with respect to traditional varieties than do traditional varieties among themselves.